The protection of personal data in Ecuador: A historical-normative review of this fundamental right in the South American country - Rosas-Lanas, Gabriela; Pila-Cárdenas, Geoconda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
ICTs are essential tools for satisfying the basic needs of human beings. However, the digital age not only brings vast benefits; it also implies multiple challenges and risks for citizens. The objective of this work is to carry out a historical review of the process of recognition of the fundamental right to the protection of personal data in Ecuador until the enactment of the Organic Law on the Protection of Personal Data in 2021. The review that we present is descriptive, using the technique exploratory and allowed us to conclude that, in Ecuador, the constitutional recognition of this right is recent.